Martian Crustal Field Influence on O+ and O2+ Escape as Measured by MAVEN. Issue 8 (20th August 2021) - Weber, Tristan; Brain, David; Xu, Shaosui; Mitchell, David; Espley, Jared; Mazelle, Christian; McFadden, James P.; Jakosky, Bruce
Abstract: Martian crustal magnetic fields influence the solar wind interaction with Mars in a way that is not fully understood. In some locations, crustal magnetic fields act as "mini‐magnetospheres, " shielding the planet's atmosphere, while in other locations they act as channels for enhanced energy input and particle escape. The net effect of this system is not intuitively clear, but previous modeling studies have suggested that crustal fields likely decrease global ion escape from Mars. In this study, we use data from the Mars Atmosphere and Volatile EvolutioN spacecraft to analyze how crustal magnetic fields influence both global and local ion escape at Mars. We find that crustal fields only increase ion escape if ions are not bound tightly to the magnetic field. Specifically, ion escape is increased only if closed magnetic fields trap 35% or less of energized oxygen ions. In any other case, crustal fields decrease both global and local ion escape by as much as 40% and 80%, respectively. This suggests that the presence of crustal magnetic fields has had a moderate impact on atmospheric ion loss throughout Martian history, potentially influencing the planet's atmospheric evolution and habitability. Plain Language Summary: The loss of the Martian atmosphere over time has transformed Mars from a potentially warm and wet planet to the cold, dry world we observe today. This atmospheric loss is often suggested to be the result of Mars losing its global magnetic field 3 billion years ago. However, the loss of a global dynamo did not leave the Martian system devoid of planetary magnetic fields. Rather, the crust of Mars still contains scattered pockets of magnetic field that extend outward into the planet's atmosphere. In some areas, these magnetic fields shield the planetary atmosphere much in the same way as the Earth's magnetic field, while in other areas the magnetic fields channel energy down into the planet's atmosphere, potentially driving enhanced atmospheric loss. In this study, we use spacecraft data from Mars Atmosphere and Volatile EvolutioN to analyze the extent to which Martian crustal magnetic fields affect atmospheric escape at Mars. We show that the shielding provided by crustal magnetic fields reduces present‐day ion escape by as much as 40%, and suggest that over time this may have been an important factor in the total amount of atmosphere lost from the planet. Key Points: We present a new method for estimating the influence of Martian crustal magnetic fields on ion escape Martian crustal magnetic fields affect global ion escape by at most 40%, decreasing escape under typical conditions Martian crustal magnetic fields affect local ion escape by at most 80%, decreasing escape under typical conditions